2020
DOI: 10.1091/mbc.e19-12-0696
|View full text |Cite
|
Sign up to set email alerts
|

Alternate histories of cytokinesis: lessons from the trypanosomatids

Abstract: Popular culture has recently produced several “alternate histories” that describe worlds where key historical events had different outcomes. Beyond entertainment, asking “could this have happened a different way?” and “what would the consequences be?” are valuable approaches for exploring molecular mechanisms in many areas of research, including cell biology. Analogous to alternate histories, studying how the evolutionary trajectories of related organisms have been selected to provide a range of outcomes can t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…First, most of the proteins identified in our study were also observed in the TOEFAZ1/CIF1 proxisome with high confidence (28). This verifies our localization of TbKifX2/TbPH1 along the whole length of the MtQ and not just the proximal end, since TOEFAZ1/CIF1 is enriched in the distal tip of a newly formed FAZ, which also incorporates a new MtQ (8,58). Second, the TbPH1 proxisome contains DLP1/2, which are involved in clathrin-mediated endocytosis (41-43) and FP45, which surrounds the flagellar pocket where endocytosis takes place.…”
Section: Discussionsupporting
confidence: 84%
“…First, most of the proteins identified in our study were also observed in the TOEFAZ1/CIF1 proxisome with high confidence (28). This verifies our localization of TbKifX2/TbPH1 along the whole length of the MtQ and not just the proximal end, since TOEFAZ1/CIF1 is enriched in the distal tip of a newly formed FAZ, which also incorporates a new MtQ (8,58). Second, the TbPH1 proxisome contains DLP1/2, which are involved in clathrin-mediated endocytosis (41-43) and FP45, which surrounds the flagellar pocket where endocytosis takes place.…”
Section: Discussionsupporting
confidence: 84%
“…In Trypanosoma, the mechanisms and proteins involved in cytokinesis are relatively well studied [9,26]. However, in Leishmania, only a few proteins, which are involved in cytokinesis, have been identified, but mechanistic details are still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…During the M phase, Leishmania spp. and all other trypanosomatids do not disassemble their nuclear envelope and perform a closed mitosis process, which is organized by spindle pole body-like structures [52]. Moreover, due to the absence of the N-terminal portion and globular domain of histone H1 and the absence of phosphorylation on serine 10 of histone H3 (H3S10), Leishmania spp.…”
Section: Leishmania Spp Cell Cyclementioning
confidence: 99%
“…Once mitosis ends, Leishmania spp. undergo a rapid remodeling in shape, first growing in length and then in width prior to cytokinesis, which ends cell division [52,55]. Although it is challenging, all these peculiarities related to the cell cycle phases may provide new routes toward the search for suitable targets for parasite cell cycle interventions aiming at their elimination.…”
Section: Leishmania Spp Cell Cyclementioning
confidence: 99%